Impact Assessment of CFLD Pulses on Pigeonpea Productivity and Profitability in Farmer’s Field - Kumar, Anjani; Kumar, Amrendra; Kumari, Pushpa; Kumar, Sujeet (Indian Journal of Extension Education, 2023)
Front line demonstration is the most appropriate method to transfer improved technology in farmer’s field. The study was conducted by ICAR-ATARI, Patna (Bihar and Jharkhand) on pigeon pea during crop season from 2019-2021. Study was conducted in 5520 number of demonstrations, altogether covering 1708.80 ha land area during the three years. Among the different varieties assessed it was observed that cv. NDA-1 and IPA-203 were outperformed in Bihar and Jharkhand respectively. The findings with respect to technology gap, extension gap and technology index of different cultivars grown were varying from 0.121 to 1.49 t/ha; 0.309 to 0.673 t/ha and 6.72 per cent to 49 per cent, respectively in Bihar and Jharkhand. The overall demonstration yield varied between 1.04 to 1.78 t/ ha which is 22.55 per cent to 71.68 per cent more than the farmer’s practices prevailing. Improved technology used under demonstration plot promoted higher yield than the local check with respect to highest net return from demonstration plot was Rs. 70365/ha and Rs. 47037.50/ha and the B:C ratio ranged from 1.33 to 2.82 and 1.02 to 2.43 in Bihar and Jharkhand respectively. Productivity and profitability can be enhanced by appropriate use of critical inputs and newer technological intervention.
Keywords: Pulses; CFLD; Pigeonpea; Extension gap; Technology gap; Technology index